2006 International Electron Devices Meeting 2006
DOI: 10.1109/iedm.2006.346777
|View full text |Cite
|
Sign up to set email alerts
|

AC NBTI studied in the 1 Hz -- 2 GHz range on dedicated on-chip CMOS circuits

Abstract: We describe on-chip circuits specially designed and fabricated for the purpose of measuring the effect of AC NBTI on an individual, well-defined device in the wide frequency range on a single wafer. The circuits are designed to allow measurements in multiple modes, specifically, DC and AC NBTI (both interrupted and on-the-fly), on a single pFET and on a CMOS inverter, as well as charge-pumping characterization of the stressed pFET. The results indicate that AC NBTI is independent of the frequency in the 1 Hz -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(68 citation statements)
references
References 4 publications
(3 reference statements)
7
61
0
Order By: Relevance
“…This property is known as frequency independence. Although several differing experimental results have been observed, recent experiments have shown that this holds good over the 1Hz-1GHz bandwidth [38], which seconds the analytical findings in [16]. However, as we move closer to DC, some form of frequency dependence is expected.…”
Section: Nbti Model For High Frequency Operationsupporting
confidence: 50%
See 2 more Smart Citations
“…This property is known as frequency independence. Although several differing experimental results have been observed, recent experiments have shown that this holds good over the 1Hz-1GHz bandwidth [38], which seconds the analytical findings in [16]. However, as we move closer to DC, some form of frequency dependence is expected.…”
Section: Nbti Model For High Frequency Operationsupporting
confidence: 50%
“…Thus, on the basis of experimental data from [38], and the trend seen in Fig. 21, we conclude that the interface trap count determined for τ = 1s, asymptotically equals the number for a case where τ = 1ns, over t life , where t life is the lifetime of the circuit, and is assumed to be 10 years of operation:…”
Section: Nbti Model For High Frequency Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of noise margin can be differentiated; low noise margin (NML) and high noise margin (NMH), which correspond with the minimum noise level signal to switch the CMOS inverter from low to high and from high to low, respectively. The NML and NMH are defined by (3) where V IL , V OL , V OH , V IH are obtained when the slope of VTC equals −1 (Fig. 3).…”
Section: Impact On Noise Marginmentioning
confidence: 99%
“…The NBTI effect on static and dynamic stress has been also reported. These investigations show that the voltage threshold shift (∆V th ) under dynamic stress is almost half of DC case, due to the recovery properties of NBTI [3]. At circuit level, the NBTI effects have not been deeply investigated.…”
Section: Introductionmentioning
confidence: 99%